Enhancing Concrete Performance and Promoting Sustainability: A Review of Natural and Synthetic Fibres for Better Workability and Mechanical Properties - Dr. Kavita Verma; Natasha Baruah; Manish Kumar Pathak; Rohit Kumar Mahto; Diamond Longjam; Abhay Verma (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Concrete is one of the most widely used building materials in the world because of its strength, durability and fire resistance. Due to rapid growth in infrastructure and residential projects, the use of concrete has increased a lot, due to which cement production has also risen significantly, and is now one of the major contributors to global carbon emission. Also, concrete has some undesirable properties as well, such as low tensile strength, brittleness, low impact resistance and cracking tendency. One of the ways through which these issues can be effectively dealt with is by using fibres in concrete to make Fibre Reinforced Concrete (FRC). The use of natural as well as synthetic fibres has got attention in recent years due to its potential to enhance the workability, durability and mechanical properties of concrete, and to reduce carbon emissions produced during cement production. This review paper aims to provide a comprehensive analysis of the different types of natural and synthetic fibres which have been studied and utilised by researchers over the years, and their impact on the properties of concrete, mainly focusing on the workability, durability and mechanical properties of concrete. An in-depth analysis of research papers from the past decade was conducted, focusing primarily on how different fibres impact the workability, durability and mechanical properties of concrete. The review paper concludes, after careful study of the advantages and disadvantages offered by the use of different fibres, that steel fibre is the most favourable fibre to be used for enhancing the performance of concrete, particularly for strength enhancement of concrete.
Keywords: Fibre; Fibre-reinforced concrete; Mechanical properties; Workability